Muhammad Uthman El Muhammady’s Response to the Threat of Religious Pluralism in Malaysia: Respons Muhammad Uthman El Muhammady Terhadap Ancaman Pluralisme Agama di Malaysia - Mohamad Kamil, Ibrahim Majdi; Mohd Khambali @ Hambali, Khadijah; Wan Ramli, Wan Adli (Jurnal Usuluddin, 2025)
This article examines Muhammad Uthman El Muhammady’s response to the spread of religious pluralism in Malaysia, which is perceived as a threat to the Islamic creed. The objective of this study is to analyze his views and critiques of figures and movements promoting pluralism, particularly the influence of John Hick and local scholars such as Mohamad Hashim Kamali. The study adopts a qualitative approach through content analysis of his major works, including books, papers, scholarly articles, and lectures. The findings reveal that Muhammad Uthman El Muhammady strongly rejects religious pluralism and emphasizes the importance of returning to the principles of Ahli Sunah Waljamaah as a safeguard for Islamic faith. The significance of this study lies in clarifying the role of local Muslim thinkers in defending orthodoxy amidst the globalization of ideas. Its implications highlight the need to develop a systematic Islamic intellectual narrative through structured creed education, exposure to Sunni epistemology, and strengthening Islamic identity within integrated educational policies. This article recommends reinforcing mainstream Islamic discourse to effectively address the challenges of religious pluralism, alongside further research on the effectiveness of these approaches in a plural society and within the context of globalized thought.